Improved detection of coronary artery disease by CZT regional coronary blood flow evaluation - Lima, R. S. L.; Bezerra, A.; Andrade, M.; Domenico, C.; De Lorenzo, A. (Frontiers in Nuclear Medicine, 2022)
Introduction: CZT cameras have enabled the noninvasive quantification of myocardial flow reserve (MFR), an important physiologic measure. This study aimed to compare the accuracy of myocardial perfusion SPECT (MPS) with or without MFR evaluation for the detection of obstructive coronary artery disease (CAD). Methods: 48 patients with CAD (>50% obstruction) detected at invasive coronary angiography or CT angiography underwent dipyridamole MPS and MFR evaluation within 30 days. A 1-day protocol (rest-stress) was used to quantify MFR. The acquisition of dynamic rest and stress images was initiated simultaneously to 99mTc sestamibi injection (10mCi e 30mCi, respectively), both lasting for 11 minutes, followed by 5-minute imaging. Pharmacologic stress with dipyridamole (0,56mg/kg for 4 minutes) was performed with the patient positioned in the CZT camera. The images were processed and time-activity curves were generated, calculating global and regional MFR in a semiautomatic software. A global or regional MFR <2 was considered abnormal. MPS perfusion images were classified as normal or abnormal. The images were interpreted by experienced physicians blinded to the results of MFR and coronary angiography/CT. Results: Mean age of the population was 61 ± 9 years, 54.2% female. Twenty patients (41.7%) had single-vessel CAD, 22 (45.8%) 2-vessel CAD and 6 (12.5%), triple-vessel CAD. Among the 82 vessels with obstruction, 48 had perfusion abnormalities in MPS and 60 had reduced MFR, while among the normal vessels, had 54 normal MPS and 52 had preserved MFR. The sensitivity of MFR (69%) was higher than that of MPS (55.2%), without significant changes in specificity (86 vs 83.7%). Conclusions: MFR in the CZT camera is more sensitive for the detection of CAD than perfusion abnormalities in MPS, especially in patients with multivessel CAD.